Hercynine, Ergothioneine and Redox State in Stallion's Seminal Plasma - Salvatore Sotgia; Andrea Taras; Angelo Zinellu; Raffaele Cherchi; Arduino A Mangoni; Ciriaco Carru; Luisa Bogliolo (MDPI AG, 2020)
The dependence of a stallion's spermatozoa on oxidative phosphorylation for energy requirements results in an unconventional relationship between reactive oxygen species (ROS) production and fertility. In such a scenario, antioxidant activity must be finely controlled and not affect the essential functions of ROS. Some in vivo evidence suggests that the naturally occurring antioxidant ergothioneine (ERT) interferes with the critical roles of ROS/reactive nitrogen species (RNS) in pro-oxidant states but not in healthy tissues. The measurement of ERT in seminal plasma collected from 14 stallions (five Anglo-Arab, five Sella Italiano and four Thoroughbreds of which three are Arabian and one English) aged 16 ± 6 years (range 6-25 years) confirms that ERT is present at high concentrations in this biological fluid, between 16.80 and 971.48 µmol/L. Although the presence of high ERT concentrations in the seminal plasma of a stallion has long been known, its exact biological role is uncertain. This might be due to the peculiar antioxidant cycle of ERT, specifically its rapid recovery, which potentially masks concentration fluctuations and, therefore, the extent of its physiological effects. The measurement of the ERT precursor and redox metabolite hercynine (ERY) may overcome such issues, as ERY does not undergo regeneration processes. ERY was detectable and measurable in the seminal plasma of all stallions at a median concentration of 7.50 (IQR 15.26) nmol/L. The analysis of the association between the ERT and ERY, as well as with other established antioxidants such as glutathione and cysteine, suggests that ERT may play a major role in the antioxidant machinery of seminal plasma, and that ERY might serve as a new combined marker of oxidative stress and semen quality.